Multi-Faceted Effects of Cannabis and Cannabinoids on the Male Reproductive System: A Review - Somenath Ghosh (International Journal of Pharma and Bio Sciences, 2020)
Cannabis sativa is a hallucinating drug used in different parts of the world from ancient time. This is used as a part of various religious and social practices. Cannabis is a special type of Marijuana which can provide temporary relief from analgesia, body pain, and some other clinical conditions. Thus, importance of Cannabis is mostly described as a narcotic analgesic agent. But, the impacts of Cannabis on the reproductive health of females and males are multi-faceted and differentially fatal. Current researches suggest that cannabis may negatively impact male and female fertility conditions. In females, Cannabis can reduce female fertility by disrupting the hypothalamic release of gonadotropin-releasing hormone (GnRH), leading to reduced estrogen and progesterone production and an ovulatory menstrual cycles. In males, cannabis can cause changes in different ways in the reproductive system. At the tissue level, under chronic administration testicular morphology is changed which can exert its effect on sperm quality. Sperm quality is marked by different parameters like semen quality, sperm morphology, sperm mortality, and sperm motility. Upon chronic cannabis treatment, it was noted that almost all of the sperm parameters are significantly reduced. Reduced sperm parameters, eventually affect male reproductive hormones i.e. testosterone, Interstitial Cell Stimulating Hormone (ICSH), Luteinizing Hormone (LH), and Follicle Stimulating Hormone (FSH). These physiological and hormonal parameters finally cause reduced libido which may even lead to oligospermia and infertility. Till date, studies delineating cannabis effect on the male reproductive system is mostly centered on rodent models and it is mostly lacking in human and in sub-human primates. Considering the primate male reproductive system, these kinds of studies are haphazard and scanty. Thus, the lacunas of previous studies were identified and the present review focuses on the effects of cannabis on the male reproductive system in a systematic manner considering human and sub-human primates in particular.